Analysis and Dynamic Optimization of Torsional Vibration Characteristic of Traction Unit of Shearer - Jia Chao; Wang Dawei (Jixie chuandong)
In order to obtain the better torsional vibration characteristics of the traction unit of the shearer,taking a new type of shearer traction drive system as the research object,based on its simplified kinetics model,by using the ADAMS software,the dynamics model is built,applies the step load and simulates the dynamic characteristics,and the potential energy curve of each elastic torsion spring is got. The torsional stiffness of the three torsion springs with the greatest potential are optimized and the optimized data are validated by using the above model,the result show that the potential energy distribution of the torsion spring is more uniform and the maximum potential energy value of each torsion spring has obviously decreased compared with the previous optimization. This method is of great significance to improve the torsional vibration characteristics of the traction unit of the shearer.